2017
DOI: 10.7717/peerj.3130
|View full text |Cite
|
Sign up to set email alerts
|

Competition and feeding ecology in two sympatric Xenopus species (Anura: Pipidae)

Abstract: The widespread African clawed frog (Xenopus laevis) occurs in sympatry with the IUCN Endangered Cape platanna (Xenopus gilli) throughout its entire range in the south-western Cape, South Africa. In order to investigate aspects of the interspecific competition between populations of X. laevis and X. gilli, an assessment of their niche differentiation was conducted through a comprehensive study on food composition and trophic niche structure at two study sites: the Cape of Good Hope (CoGH) and Kleinmond. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
1
29
1
Order By: Relevance
“…The diet of X. laevis has been studied in its native range (Schoonbee, Prinsloo & Nxiweni, 1992; Vogt et al, 2017), and in different invasive populations (McCoid & Fritts, 1980; Measey, 1998a; Lobos & Measey, 2002; Faraone et al, 2008; Amaral & Rebelo, 2012; Courant et al, 2014). The first study carried out in the native range was performed in a fish farm (Schoonbee, Prinsloo & Nxiweni, 1992), which does not necessarily represent the typical diet of native populations.…”
Section: Discussionmentioning
confidence: 99%
“…The diet of X. laevis has been studied in its native range (Schoonbee, Prinsloo & Nxiweni, 1992; Vogt et al, 2017), and in different invasive populations (McCoid & Fritts, 1980; Measey, 1998a; Lobos & Measey, 2002; Faraone et al, 2008; Amaral & Rebelo, 2012; Courant et al, 2014). The first study carried out in the native range was performed in a fish farm (Schoonbee, Prinsloo & Nxiweni, 1992), which does not necessarily represent the typical diet of native populations.…”
Section: Discussionmentioning
confidence: 99%
“…Xenopus laevis (African Clawed Toad), native to South Africa but traded intensively globally, hybridises with the endemic X. gilli (Cape Platanna) (Picker 1985), but importantly there is no evidence of introgression (Furman et al 2017). Even though these two species might have likely overlapped for millennia (Schreiner et al 2013), densities of X. leavis have probably been artificially increased in the last 400 years (Measey et al 2017), leading to intense competition and predation (Vogt et al 2017;de Villiers et al 2016). Sclerophrys gutturalis (Guttural Toad), native to much of the country but introduced to a peri-urban area of Cape Town (Vimercati et al 2017), could potentially threaten the native endangered Sclerophrys pantherina (Western Leopard Toad), but no evidence of the extent of this threat has been reported to date (Measey et al 2017).…”
Section: Amphibiansmentioning
confidence: 99%
“…However, the original range of X. laevis remains unclear (Measey et al 2017). Furthermore, research strongly suggests that the presence of X. laevis in the same water bodies reduces recruitment of X. gilli through competition and predation (De Villiers et al 2016;Vogt et al 2017;Thorp et al 2019). Early research suggested that introgression was a threat to X. gilli (Picker et al 1996), and this formed the basis of NEM:BA listing hybrids of X. gilli and X. laevis for removal.…”
Section: Xenopus Laevis (African Clawed Frog)mentioning
confidence: 99%